2000
DOI: 10.1590/s0004-282x2000000200005
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal sleep pattern in native Brazilian Terena adults

Abstract: -Social-economic factors influence sleep habits. This research analyzes characteristics of nocturnal sleep in Brazilian Native Terena adults. Sixty-four adults (31 M; 33 F) from 18 to 75 years, with a mean age of 37.0, from the Indian Reservation village of Córrego do Meio, in the central region of Mato Grosso do Sul, an agriculturally oriented group were evaluated. Nocturnal sleep characteristics were evaluated by means of a standard questionnaire applied to each individual. It was observed that reported noct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…The discrepancies in chimpanzee data illustrate the need to gather sleep quota data on chimpanzees using non-invasive methods such as the infrared videography used in this study. Although the sleep duration exhibited by orang-utans in this study was longer than western human volunteers studied in controlled environments, the value falls within the range of durations reported for aboriginal populations (7-10 h) of New Guinea and South America (Siegmund et al, 1998;Reimao et al, 2000). Around sunset, individuals locate a sleep location and gather bed materials (see methods for detail on materials) to manufacture a sleeping platform.…”
Section: Discussionsupporting
confidence: 57%
“…The discrepancies in chimpanzee data illustrate the need to gather sleep quota data on chimpanzees using non-invasive methods such as the infrared videography used in this study. Although the sleep duration exhibited by orang-utans in this study was longer than western human volunteers studied in controlled environments, the value falls within the range of durations reported for aboriginal populations (7-10 h) of New Guinea and South America (Siegmund et al, 1998;Reimao et al, 2000). Around sunset, individuals locate a sleep location and gather bed materials (see methods for detail on materials) to manufacture a sleeping platform.…”
Section: Discussionsupporting
confidence: 57%
“…A few other studies have examined sleep in non-Westernized or developing areas (see Table 3). For example, a study among the Native Terena, a rural agricultural group in Brazil, found that they spent an average of 9 h in bed, went to bed at 20:43 and woke at 6:06 on weekdays for all age groups combined (Reimão et al, 2000). Despite being based on self-report, average bedtime, and time in bed were similar to the averages in the Haiti sample; however, average wake time in the Native Terena was approximately 1 h later.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have examined sleep in communities outside of the United States, Europe, and Japan. These have included a study among an agricultural population in Brazil, the Native Terena (Reimão et al, 2000), a study of men in Abidjan, a large city in the Ivory Coast (Bogui et al, 2002), a study among college students in Mexico City, among college students in Ethiopia (Lemma et al, 2012) and among college students in Nigeria (Oluwole, 2010). The primary limitation of all of these studies is that they relied on self-reported sleep duration and timing.…”
mentioning
confidence: 99%
“…The cross-cultural study of human sleep expression, sleep architecture (distribution of NREM and REM throughout a nightly sleep bout), diurnal bouts of inactivity (i.e., napping and/or energy conservation), and sleep quality is in its infancy [46][47][48][49]. The sociophysical ecology of human sleep is more readily accessible in historical and ethnographic records, yet the only data relative to forager sleep expression is anecdotal.…”
Section: Advances In Zoologymentioning
confidence: 99%